Linked Open Data em coleções de patrimônio cultural: aspectos da representação da informação para Humanidades Digitais - Ninin, Débora Marroco (2018)
Introduction: The emergence of the Internet and the Web platform raise new possibilities and challenges of management and access to knowledge, stored in digital environments in the form of data. In this context, the tools for description promoted by the Linked Open Data movement are highlighted, through Linked Data principles. The connection and availability of cultural heritage data, present in libraries, archives and museums, offer new possibilities for learning and dissemination of knowledge in Humanities and the vast cultural heritage distributed throughout the globe. Given this scenario, the question is: how do Linked Data principles contribute to the representation and access to cultural heritage collections? Purpose: To analyze the Linked Open Data in cultural heritage institutions, in order to contribute to studies about representation and access to cultural heritage collections. Methodological procedures: This is an exploratory theoretical-applied research, with a qualitative approach, carried out through a bibliographical and documentary survey about the research question. The scientific bibliography and relevant documents were analyzed in order to provide support for the representation and promotion of access to the cultural heritage collections within the scope of the Linked Open Data movement. Results: The results achieved included 1) academic contributions regarding the benefits of using the tools of the Linked Open Data movement, highlighting issues of interoperability (technical and semantic) and data sustainability, 2) the survey of Linked Open Data initiatives in international cultural heritage institutions, 3) the presentation and discussion of data models adopted by the initiatives Europeana and DPLA and the data scheme of the DigitalNZ project and 4) presentation of the solutions developed by the cultural heritage community to use the metadata standards for the Linked Open Data description of cultural heritage collections. These results demonstrated that the cultural heritage community has sought to take advantage of the benefits offered by the Linked Open Data movement, especially with respect to the sustainability of the processes of description and access to the data of cultural heritage collections and, with that, this community seeks to approach the practices and goals proposed by the Digital Humanities discipline.